PENGARUH KUALITAS PRODUK, HARGA, DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING PADA SMARTPHONE XIAOMI DI KOTA PEKANBARU (Studi Kasus Pada Mahasiswa Universitas Riau) - Muhammad, Hidayatullah Amin; Taufiqurrahman, Taufiqurrahman; Tengku, Musfar Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
The purpose of this research is to analyze the significance of the influence ofproduct quality (X1), price (X2), and lifestyle(X3) on purchasing decisions(Y) withbrand image(Z) as an intervening variable on Xiaomi smartphones in the city ofPekanbaru, with a case study on students of the University of Riau. This researchis a case study with a quantitative method approach. The subjects of the researchare students of the University of Riau in Pekanbaru as respondents. data collectionusing questionnaires, observations, and also interviews. In this study, the modeland data analysis technique used the path analysis approach. Before conductingthe Path Analysis, instrument quality tests and classical assumption tests were firstcarried out, along with hypothesis testing processed using the SPSS (StatisticalProgram for the Social Sciences) version 26 for Windows, with 96 respondents.The research results show that product quality, price, and lifestyle significantlyinfluence purchasing decisions with brand image as an intervening variable inXiaomi smartphones. Where The product quality obtained a t-value (2.225), theprice t-value (2.074), the lifestyle t-value (2.652), and the brand image t-value(7.203) are greater than the t-table value (1.986). Keywords: product quality, price, lifestyle, purchase decision, and brand image.